2022
DOI: 10.55446/ije.2021.137
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Incidence of Striped Flea Beetle Phyllotreta striolata F. on Cruciferous Crops in North Kashmir

Abstract: This study is on the seasonal incidence of Phyllotreta striolata F. during 2015 and 2016, on turnip (Brassica rapa var. rapa), radish (Raphanus sativus) and cabbage (B. oleracea var. capitata). The incidence observed at weekly intervals was correlated with weather factors. The pest was first observed during 35th standard meteorological week (SMW), and in 2015, peak was observed on turnip (22.8 beetles/ plant) and radish (22.2 beetles/ plant) during the 40th SMW; during 2016, peak was (19.4 beetles/ plant on tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…The maximum population of striped flea beetles (11.5 to 12.6 beetles/plant) was found in March during both years. The present finding may be supplemented with the results of Anooj et al [43] and Rasool and Lone [62], who reported up to 22.2 beetles/plant in radish, though the values were much higher compared to the findings of this study. The findings are also in line with Patel et al [63], who observed the incidence of P. cruciferae G. from the first week of October till the first week of December.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The maximum population of striped flea beetles (11.5 to 12.6 beetles/plant) was found in March during both years. The present finding may be supplemented with the results of Anooj et al [43] and Rasool and Lone [62], who reported up to 22.2 beetles/plant in radish, though the values were much higher compared to the findings of this study. The findings are also in line with Patel et al [63], who observed the incidence of P. cruciferae G. from the first week of October till the first week of December.…”
Section: Discussionsupporting
confidence: 72%
“…Similarly, Ghosh [64] reported a non-significant positive correlation of flea beetle infestations with maximum temperature, but a negative correlation with weekly total rainfall. The incidence of flea beetles revealed a positive influence of temperature and sunshine hours on the population build-up of flea beetles, but a negative effect of rainfall and relative humidity [62]. Dubale et al [65] studied the abundance of flea beetles in ridge gourd and found that flea beetle infestation was positively correlated with maximum temperature, and relative humidity in a non-significant manner, but negatively correlated with minimum temperature and rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…For the sprouting -rosette period, the most harmful is the complex of crucifer flea beetles (Phyllotreta), which includes the following species: black flea beetles (Phyllotreta atra F.) (28-33.6% by number in the structure of flea species diversity), Phyllotreta nemorum L. (4.7-6.3%), Phyllotreta undulata Kutsch, (0.3-0.6%), Phyllotreta nigripes F. (53.4-61.5%), Phyllotreta F. (5.5-6.1%, respectively) (Tsytsiura, 2016;Gikonyo et al, 2019). It was determined that the decrease in yield of cruciferous crops from damage by various types of fleas at the seedling-rosette stage can reach an interval of 30-70%, depending on the degree of damage (Heath, 2017;Rasool & Lone, 2022). Given the fact that the primary and most important assimilation of cruciferous crops, including oilseed radish, is carried out by cotyledons, and the duration to the formation of the first pair of true leaves depending on climatic conditions can range from 6 to 20 days, the study of pest severity of crucifer flea beetles dominating the primary stage of plant growth processes is relevant (Heath, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The damage to cotyledons by fleas causes disruption of the photosystem activity of its assimilation surface (Rasool & Lone, 2022). There was a definite link between the damage degree caused by the respective pest to the assimilating surface and the underlying physiological transformations in the plant organism's photosystem (Pérez-Bueno et al, 2019; Arnold et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Thakur et al (2009) recorded the pest from north-east India. Rather et al (2017) and Rasool and Lone (2022) studied the seasonal occurrence of P. striolata on brassicaceous vegetables in Kashmir. Phyllotreta striolata was known only from the Andaman and Nicobar Islands, Kashmir, north-east India and West Bengal in India till Anooj et al (2020) reported its outbreak on radish, Raphanus sativus L. in Delhi and Haryana.…”
mentioning
confidence: 99%